2016
DOI: 10.3390/nu8020088
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Fortified Condiments and Noodles to Reduce Anemia in Children and Adults—A Literature Review and Meta-Analysis

Abstract: Micronutrient deficiencies impose a considerable burden of disease on many middle and low income countries. Several strategies have been shown to be effective in improving micronutrient deficiencies. However, the impact of fortified condiments as well as fortified noodles is less well documented. We aimed to investigate existing evidence on the impact of micronutrient fortified condiments and noodles on hemoglobin, anemia, and functional outcomes in children and adults (age: 5 to 50 years). We conducted a lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
0
15
0
2
Order By: Relevance
“…Nonetheless, the relative impact of these factors has not been comprehensively evaluated. The efficacy of iron fortification of already assessed condiments on increasing hemoglobin levels and decreasing the risk of anemia is well-established, particularly for double-fortified salt with iodine and iron [12][13][14]. The effectiveness of these interventions is less documented and, although hemoglobin and ferritin levels may slightly increase, in some instances the prevalence of anemia does not change in the population [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the relative impact of these factors has not been comprehensively evaluated. The efficacy of iron fortification of already assessed condiments on increasing hemoglobin levels and decreasing the risk of anemia is well-established, particularly for double-fortified salt with iodine and iron [12][13][14]. The effectiveness of these interventions is less documented and, although hemoglobin and ferritin levels may slightly increase, in some instances the prevalence of anemia does not change in the population [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of iron fortification of already assessed condiments on increasing hemoglobin levels and decreasing the risk of anemia is well-established, particularly for double-fortified salt with iodine and iron [12][13][14]. The effectiveness of these interventions is less documented and, although hemoglobin and ferritin levels may slightly increase, in some instances the prevalence of anemia does not change in the population [13,14]. Furthermore, results regarding the role of potentially influencing factors affecting the outcome of the interventions are often mixed, show no effect or are not reported [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se han propuesto varias estrategias, con el fin de prevenir o reducir el impacto de la anemia y las deficiencias nutricionales, especialmente en población menor de cinco años. Se encuentran ejemplos como suplementos en alimentos, incrementando la densidad de energía y la carga de micronutrientes en los mismos; también existe la fortificación casera con aspersión de micronutrientes en polvo (intervención de interés en el presente estudio), así como suministro de cápsulas de vitamina A, a intervalos definidos (Who/Fao, 2006) (Hess, Tecklenburg, & Eichler, 2016).…”
Section: Introductionunclassified
“…The implementation of iron fortification in condiments and commonly consumed food vehicles has shown to be effective as this strategy focuses on fortifying regularly consumed condiments, eliminating concern of adherence and affordability (153). A recent meta-analysis analyzed the comparison of iron status outcomes from iron fortified condiments compared to noodles (154). The review found a significant increase in hemoglobin of adults and children consuming iron-enriched/fortified condiments in comparison to noodles, 0.74g/dL Hb and 0.3g/dL Hb, respectively (154).…”
Section: Fortificationmentioning
confidence: 99%